Cultivation of plant-growth promoters in vinasse: contributions for a circular and green economy - Torres, Mariela Analía (2022)
Vinasse is a by-product with a key role in the circular economy. In this work, we analyze sugarcane vinasse as culture medium for obtaining single and mixed inoculants. Trichoderma harzianum was cultured in single and sequential co-culture with Pseudomonas capeferrum or Rhizobium sp. Fungal biomass was higher in vinasse than in a laboratory medium. Residual vinasses presented almost neutral pH and lower conductivities and toxicity than raw vinasse. Fertigation with residual vinasses improves characteristics of soil evidenced in the total N, cation exchange capacity, urease and acid phosphatase, and the microbial metabolic diversity, in comparison to raw vinasse. The evaluation of the treatment indicates that vinasse is suitable for the production of inoculants containing T. harzianum and that the co-culture with P. capeferrum improves the characteristics of the residual vinasse in comparison to Rhizobium sp. Obtaining this valuable biomass in vinasse is relevant for the circular and green economy.